Business Research Methodology Learning Strategies through Participatory Action Research - วิริยะสืบพงศ์ เพชรรัตน์ (Sripatum Review of Humanities and Social Sciences, 2018)
Learning strategies on business research methodology applicable for the 21st century is based on systematic approaches. The learning of business research methodology through participatory action research includes formulating questions by three systematic approaches of practice, reflection, and interpretation through mechanism of learner, educator, and methods including resource management based on learners and activities to achieve desired goals. The results are the learning of research on the actual livelihood of fishing villagers of Ban Pak Khlong Village. The learners can formulate research problems to solve their problems resulting in the benefits to the community and conduct the research until completion of the research report. The results help the learner and teacher to develop together the creativity of problem formulation, respecting villagers and industry representatives, synthesis thinking by collecting relevant literature, scrutinizing management theories to answer the research questions, establishing the holistic system, and presenting a new form of research. Furthermore, through learning and discipline processes, the research can be completed and the results can then be presented and be beneficial to the community and relevant industries. Finally, it is the learning of ethics and the pride of collaborating to contribute via research to the local development which can be used as a source for future study in the next three years. Anyway, both the learner and teacher should strictly adhere to Itthibat 4, the four basic principles for success, namely, Chanda or aspiration, Viriya or perseverance, Citta or dedication, and Vimansa or reasoning, which will enable them to work and learn happily.